2018
DOI: 10.12688/f1000research.15475.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunisation: What have been the gains? Where are the gaps? What does the future hold?

Abstract: The vaccination of pregnant women has enormous potential to protect not only mothers from vaccine-preventable diseases but also their infants through the passive acquisition of protective antibodies before they are able to themselves acquire protection through active childhood immunisations. Maternal tetanus programmes have been in place since 1989, and as of March 2018, only 14 countries in the world were still to reach maternal neonatal tetanus elimination status. This has saved hundreds of thousands of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Pregnant women are considered at high risk for severe influenza disease, for this reason, influenza vaccination has been recommended for pregnant women and introduced into immunization programs (84). Influenza vaccination is safe and protective on preterm birth (PTB) and low birth weight (LBW) (85).…”
Section: Neonatal Immunity and Viral Infectionsmentioning
confidence: 99%
“…Pregnant women are considered at high risk for severe influenza disease, for this reason, influenza vaccination has been recommended for pregnant women and introduced into immunization programs (84). Influenza vaccination is safe and protective on preterm birth (PTB) and low birth weight (LBW) (85).…”
Section: Neonatal Immunity and Viral Infectionsmentioning
confidence: 99%
“…Thus, infants appeared to be exposed to pertussis before developing vaccine-induced immunity, being the vaccination coverage at 24 months old extremely high in the study period. It was demonstrated that hospitalizations due to pertussis disproportionately affect children less than three months of age [24].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing antenatal care frequency improves the neonatal mortality reduction (11)(12)(13)(14)(15). Similarly, several studies demonstrated that maternal iron and folic acid supplementation (16)(17)(18)(19)(20)(21)(22), tetanus toxoid vaccination of mothers (16,(23)(24)(25)(26) sleeping under insecticide impregnated bed net during pregnancy (10) and syphilis screening (22) significantly reduces neonatal mortalities.…”
Section: Introductionmentioning
confidence: 97%